2017
DOI: 10.14295/oh.v23i4.1080
|View full text |Cite
|
Sign up to set email alerts
|

Germination test and ornamental potential of different basil cultivars (Ocimum spp.)

Abstract: Basil (Ocimum spp.) is an essential oil producing plant and it is used as a condiment for diferent foods, besides serving as raw material for medicinal purposes. This crop has also been showing great importance as an ornamental plant in recent years. However, basil lacks studies concerning its different usages with special regards to its ornamental potential. Therefore, this study aimed at evaluating the vegetative development and the ornamental potential of the basil cultivars ‘Grecco a Palla’ (O. minimum), ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Thus, it appears that the proposed methodology works in the experimental quality control of seed germination. A previous studies presented that cultivar 'Grecco a Palla' (V6) presented superior seed germination percentage and seedling development when compared to 'Thai Basil' and 'Alfavaca Basilicão Vermelho' (V2) (França et al, 2017), in agreement with our results. Low %G values are quite worrying in terms of costs.…”
Section: Resultssupporting
confidence: 93%
“…Thus, it appears that the proposed methodology works in the experimental quality control of seed germination. A previous studies presented that cultivar 'Grecco a Palla' (V6) presented superior seed germination percentage and seedling development when compared to 'Thai Basil' and 'Alfavaca Basilicão Vermelho' (V2) (França et al, 2017), in agreement with our results. Low %G values are quite worrying in terms of costs.…”
Section: Resultssupporting
confidence: 93%
“…The shortest number of days to start of flowering i.e. earliest (39 days) was recorded s from O. americanum L. Such variation in number of days to start of flowering was also reported by França et al(2017) who indicated that 'Grecco a Palla' cultivar bloomed 40 days after sowing, whereas 'Thai Basil' developed inflorescences 48 days after sowing, Alfavaca Basilicão Vermelho' displayed inflorescences 55 days after sowing.…”
Section: Number Of Days To Start Of Floweringsupporting
confidence: 64%
“…It was verified that plant diameter directly interferes in the quantity and volume of leaves, being an essential characteristic for both the commercialization of the plant in natura and for oil extraction. For the extraction of essential oil, plants with a greater number of leaves-that is, greater diameter-are of interest as it will be extracted from these structures [25]. For the percentage of branches with inflorescence, inflorescence branch length, seed maturation and weight, no significant differences were observed among the accessions.…”
Section: Accessionsmentioning
confidence: 99%
“…It was verified that plant diameter directly interferes in the quantity and volume of leaves, being an essential characteristic for both the commercialization of the plant in natura and for oil extraction. For the extraction of essential oil, plants with a greater number of leaves-that is, greater diameter-are of interest as it will be extracted from these structures [25]. Internode length and leaf blade width and length were higher in the broad leaf accessions than in the those with narrow leaf, and the mean of leaf blade length in the broad leaf accession was of 2.92 cm, being higher than in the narrow leaf accession (1.38 cm).…”
Section: Accessionsmentioning
confidence: 99%